Dispute Resolution between Players and Clubs after the Enactment of Law Number 11 Year 2022 Concerning Sports - Arinto Nugroho; Eny Sulistyowati; Emmilia Rusdiana; Muh. Ali Masnun; Eko Wahyudi; Rezi Wanda Huzaimi; Denial Ikram (Technium Social Sciences Journal, 2023)
Disputes between players and sports clubs usually occur because one of the parties violates the promise as agreed in the contract. There are differences in dispute resolution in similar cases in Indonesia. There were those who filed lawsuits at the District Court and there were those who complained to FIFA where FIFA then imposed sanctions on the club. This non-uniformity creates confusion especially for those who wish to question the rights that should be obtained. Based on this, the purpose of this study was to understand whether the courts have the authority to resolve disputes between players and sports clubs in Indonesia after the promulgation of Law Number 11 of 2022 concerning Sports. The research method used is normative law with a prescriptive analytical approach. The results of the study show that currently the court has no authority to adjudicate disputes between players and clubs. This has consequences, namely the resolution of disputes becomes more efficient in time but in terms of the right to obtain justice it becomes limited because the settlement by arbitration is final and binding so that no further legal action can be taken.